MODERASI CORPORATE GOVERNANCE TERHADAP HUBUNGAN ASIMETRI INFORMASI DENGAN MANAJEMEN LABA - SABILA SYAHYIDATI, SAL; VENUSITA, LINTANG (Jurnal Akuntansi AKUNESA, 2018)
Profit is one of the potential information in financial statements. The right information as a way to avoid information asymmetry. The occurrence of information asymmetry can be controlled by using a concept of corporate governance. These research purpose to test the influence of composition the board of commissioner in moderating relationship by information asymmetry with earnings management. This research by using panel data that taken from the Indonesia Stock Exchange with 131 samples from the manufacturing sector during the period 2015-2016. This research uses moderation regresion analysis. The results of this research provide empirical evidence that information asymmetry has a positive effect on earnings management. Corporate governance which is proxied by the composition of the board of commissioner is able to moderate and strengthen the relationship of information asymmetry on earnings management.